New Comparative Data on the Long Bone Microstructure of Large Extant and Extinct Flightless Birds - Aurore Canoville; Anusuya Chinsamy; Delphine Angst (Diversity, 2022)
Here, we investigate whether bone microanatomy can be used to infer the locomotion mode (cursorial vs. graviportal) of large terrestrial birds. We also reexamine, or describe for the first time, the bone histology of several large extant and extinct flightless birds to (i) document the histovariability between skeletal elements of the hindlimb; (ii) improve our knowledge of the histological diversity of large flightless birds; (iii) and reassess previous hypotheses pertaining to the growth strategies of modern palaeognaths. Our results show that large extinct terrestrial birds, inferred as graviportal based on hindlimb proportions, also have thicker diaphyseal cortices and/or more bony trabeculae in the medullary region than cursorial birds. We also report for the first time the occurrence of growth marks (not associated with an outer circumferential layer-OCL) in the cortices of several extant ratites. These observations support earlier hypotheses that flexible growth patterns can be present in birds when selection pressures for rapid growth within a single year are absent. We also document the occurrence of an OCL in several skeletally mature ratites. Here, the high incidence of pathologies among the modern species is attributed to the fact that these individuals were probably long-lived zoo specimens.